ANALISIS JARINGAN KOLABORASI DALAM PENCEGAHAN DAN PENANGGULANGAN HIV/AIDS: STUDI DI KABUPATEN SUBANG JAWA BARAT - Sam'un Jaja Raharja; Dede Akhmad (Jurnal Kependudukan Indonesia, 2019)
There is an increasing trend of people living with HIV/AIDS (PLWHA) in Subang District, a region characterized by high population mobility. Hence, this study aims to explain the factors that influence collaboration in HIV/AIDS prevention and control in Subang Regency. This study uses a latent construct of collaboration reflected by five dimensions: governance, administration, organizational authority, mutuality, and norms. This study uses quantitative methods and data collection techniques through distributing questionnaires to 72 respondents involved in HIV/AIDS prevention and prevention in Subang Regency. The selection of respondents represents government and non-government organizations based on quota sampling. Data were analyzed by Partial Least Square-Structural Equation Modeling (PLS-SEM) in the second order confirmatory factor analysis to explain the collaboration measurement model as a latent construct. The results showed that all dimensions of the collaboration construct were valid and reliable. All dimensions can be said to significantly explain the collaborative construct of HIV/AIDS prevention and care. The dimensions of governance are the most valuable factors that influence the construct of collaboration, followed by organizational autonomy, administration, mutuality, and finally norms as dimensions with the smallest contribution value to collaboration.Â